RETURN ON EQUITY, CURRENT RATIO, FIRM SIZE TERHADAP HARGA SAHAM DENGAN STRUKTUR MODAL SEBAGAI VARIABEL INTERVENING (Studi Kasus Perusahaan Sektor Real Estate Yang Terdaftar di BEI Tahun 2017-2020) - Merlyn Junita; Didin Fatihuddin; Anita Roosmawarni; Budi Wahyu Mahardhika (PROCEEDING UMSURABAYA, 2022)
The real estate sector is one of the most important sectors in contributing to the economy of a country. The share price growth of the real estate sector reached its peak and experienced a very high increase in 2018-2019. The up and down of stock prices are reflected in changes in stock prices that fluctuate every second. This research method is descriptive quantitative. The sampling method of this research used purposive sampling technique with a total sample of 13 companies. The data processing technique uses Partial Least Square (PLS) version 2.0 and uses the Sobel test. The results of the hypothesis test show that there is an effect of return on equity and firm size on stock prices. The results of the study the value of R-Square on Y was 0.244 or 24.4%. Because the value is less than 25%, it can be categorized that the influence of all constructs on Y is weak. While the research value of R-Square effect simultaneously or simultaneously X1, X2 and X3 to Z is 0.12 or 12%. Because the value is less than 25%, it can be categorized that the influence of all constructs on Z is weak.Keywords: Current Ratio; Firm Size; Stock Price; Return On Equity; Capital StructureÂ